Effect of Kinesiology Tape on Tri-Axial Accelerometry during the Dance Aerobic Fitness Test. Issue 3 (September 2021) - Moulder, Stephanie; Armstrong, Ross; Greig, Matt; Brogden, Chris
Objectives: Kinesiology tape (KT) is thought to provide greater mechanical support during physical activity, however, there is a paucity of research investigating its application in dance. The study aimed to determine whether KT reduces PlayerLoad (PL) during the Dance Aerobic Fitness Test (DAFT) in addition to examining the relative sensitivity of ac-celerometer site locations. Methods: University-level dancers (N = 11; age 18 ± 0.45 years, height 168.17 ± 12.25 cm, body mass 57.50 ± 9.91 kg) participated in two trials of the DAFT protocol in two conditions: no tape (NT) and kinesiology tape (KT). Global positioning systems (GPS) and accelerometer units were attached onto the seventh vertebra (C7) at the mid-scapula region and lower limb (LL) located at the mid-gastrocnemius of the dominant leg calculating measurements of triaxial (PLTotal ) and uniaxial measures (anteroposterior [PLAP], mediolateral [PLML], and vertical [PLV]) measures of PlayerLoad during the DAFT. Results: No significant main effect was observed for the taping condition in all measures of PlayerLoad (P > 0.10). A significant main effect (p < 0.01) was observed for unit location and time, with greater loading at the LL compared to C7 and during each consequent stage of the DAFT. No significant (p > 0.52) location*taping, nor location*taping*time (p > 0.36) interactions were observed for all variables measured. Conclusions: Kinesiology tape does not reduce loading patterns in healthy dancers during a fatigue protocol. However, triaxial accelerometers provide adequate sensitivity when detecting changes in loading, suggesting the LL may be deemed as a more relevant method of monitoring training load in dancers.